Pengambilan Keputusan Multi Kriteria: Kajian Teoritis Metode dan Pendekatan Dalam Pemilihan Pemasok - Ilyas Masudin; Mardila Galuh Fitri Ayni (Jurnal Ilmiah Teknik Industri, 2018)
This article attempts to explore and review methods and approaches in the Supplier selection process. Review of articles related to the approach in supplier selection that includes identification, evaluation and contract activities with suppliers is reviewed based on the quantitative and qualitative models conducted in this article. In this article, a discussion of supplier selection methods previously investigated by researchers is done through literature review published in several reputable journal database. 86 journal articles successfully collected and reviewed related methods and approaches used by researchers in memeilih supplier. From the results of this study can be concluded that the method of supplier selection through qualitative and quantitative approach is then subdivided into 4 categories with 18 methods discussed.